Chorda tympani nerve function after myringoplasty - Sham, E.H.; Prepageran, Narayanan; Raman, Rajagopalan; Quek, K.F. (Malaysian Medical Association, 2007)
This is a cross-sectional study design aimed to determine the prevalence of Chorda Tympani Nerve (CTN) injury and related symptoms following myringoplasty. Thirty patients were included in this study. The methods used were measuring taste thresholds using electrogustometer to map taste threshold on the anterior two-third of the tongue on the operated side with the non operated side as the control. Reading is taken when the subject experiences sour/metallic taste. All corresponding threshold values and findings were recorded and compared to control. Results showed 50% of patients had elevated threshold levels suggestive of CTN injury. However, none of the patients reported subjective taste loss. This study concludes that the prevelance rate of CTN injury in post myringoplasty patients is about 50% but this is not associated with altered taste sensation.